Factors Associated with Adverse Events Related to Topical Whitening Products Used among College Female Students in Sudan - Suha Gafar Mohamedkhair; Lafi Munira; Ahmed Mohammed Alamin; Pramon Viwattanakulvanid (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
This study aimed to explore the factors associated with adverse events related to topical whitening products used and to explore the reasons for using topical whitening products among female students in Sudan. A cross-sectional study was conducted from September to October 2023 in Sudan. The Medicine and Pharmacy programs were purposively selected as the study area. The total sample size was 208 participants. The self-administered questionnaire was constructed with a total of seventeen questions. For data analysis, we performed descriptive statistics analysis, bivariate analysis with simple logistic regression, and multivariable analysis with binary logistic regression presenting with adjusted odds ratio (AOR) and 95% confidence interval (95% CI). The results imply that students with middle household income were 93% less likely to get adverse events compared to those students with low household income with p-value = 0.030 (AOR: 0.07, 95% CI: 0.06 ,0.77). Students who have tested the topical whitening products before using them were 99.9% less likely to get adverse events compared to those who do not test, with p-value = <0.001 (AOR: 0.001, 95% CI: 0.001,0.00). Students who shared whitening products with family/friends were 89% less likely to get adverse events than those who do not share with p-value = 0.009 (AOR: 0.11, 95% CI: 0.021, 0.57). Furthermore, students who used whitening products with added water or other agents to whitening products were 95% less likely to get adverse events compared to those who did not use with p-value = 0.038 (AOR: 0.05, 95% CI:0.02, 0.84). The top two reasons respondents for using topical whitening products were acne (26.9%) and for beautification (24.5%). The study suggested the local government and health sectors should educate and raise the awareness of the safety of whitening products use among female students.Keywords: Adverse events, female students, Sudan, Whitening topical products